Platelet lysate-sodium hyaluronate gel promotes diabetic foot wound healing by regulating oxidative stress and autophagy - Chunyu Wang; Yangli Zhang; Hailong Yang; Li Zhou; Zhiwei Xu; Chaojie Jin; Liang Zhou; Letian Shan; Hui Wang (PLoS ONE, 2025)
Diabetic foot ulcer (DFU) is a major complication of diabetes which is difficult to heal and has high recurrence rates. It often requires amputation and even causes death, imposing significant economic burden on the society. Moreover, the current treatment options are not sufficiently effective, necessitating the search for novel treatments. In this study, therapeutic effect and mechanisms of platelet lysate-sodium hyaluronate gel (PL-HA gel) in the treatment of DFU were studied. Initially, the PL-HA gel was examined for quality control, and then the expression of growth factors (GFs) content in PL was determined. The results demonstrated high expression of GFs in PL and the gel exhibited a porous microstructure, which allowed continuous release of PL to achieve its therapeutic effects. In vivo model of type II diabetic rats was established to clarify the therapeutic effect of PL-HA gel and the mechanism by which the PL exerted therapeutic effects was further explored in HUVECs and HSFs. In vivo experiments indicated that PL-HA gel promoted wound epithelialization, collagen deposition, Cytokeratin and angiogenesis, as well as suppressed the expression of Beclin-1 and LC3 levels, while up-regulating that of P62. It also increased the SOD and MDA levels, promoted antioxidant effects, to accelerate the recovery of wounds. In vitro experiments revealed that PL could promoted wound healing by modulating oxidative stress-related parameters (ROS, SOD) and autophagy-related parameters (ULK1, P62, LC3, Beclin-1). In summary, treatment with the PL-HA gel improved diabetic wounds healing by suppressing oxidative stress and autophagy. The PL dissolved in the gel not only increased its efficacy but also ensured its safety and reliability, demonstrating the promising potential of PL-HA gel to treat DFU.